Are global gold futures returns volatilities and trading activities threshold cointegrated?. Issue 5 (7th May 2021) - Chen, Chien-Hung; Lee, Nicholas; Chang, Fu-Min; Lan, Li-Peng
Abstract : Purpose: This study aims to examine whether global gold futures returns volatilities and trading activities are threshold cointegrated. Design/methodology/approach: This study considers 11 gold futures markets, including 3 developed futures markets and 8 developing futures markets. This study also analyzes futures trading activities for speculators and hedgers. This study uses a nonlinear threshold vector error correction model (TVECM) and a threshold Lagrange multiplier (LM) test proposed by Hansen and Seo (2002) . Findings: The findings show that global gold futures return volatilities (FRV) and trading activities are not always threshold cointegrated. Most developed futures markets exhibit threshold cointegrated of gold FRV and trading activities for speculators and hedgers, whereas some developing futures markets exhibit threshold cointegrated. It suggests that speculators and hedgers trading activity conveys valuable information about changes in market volatility dynamics. On the other hand, responses to error-correction effect among gold FRV and trading activities for speculators and hedgers are dramatically different for developed and developing gold futures markets, respectively, particular in the unusual regime. Research limitations/implications: Research results show that threshold cointegration between global gold FRV and trading activities matters but not always. Thus, threshold relations have improved the authors' understanding of global gold futures price discovery process with a threshold. For research limitations, this study uses only near month futures contracts, as it contains more information but not using far month contracts. Practical implications: The findings may have important trading implications with additional insights in a(n) (un)usual regime further regulation may be detrimental to the price responsiveness in futures markets if increased price volatility and trading volume are attributed to liquid and efficient markets. Social implications: The findings may have important policy implications with additional insights. For example, in a(n) (un)usual regime greater regulatory restrictions may be warranted to decrease market inefficiencies if increased price fluctuations are caused by increased trading volume. Policymakers could enhance futures trading liquidity or restrict speculating positions. Originality/value: This study examines whether global gold futures returns volatilities and trading activities are threshold cointegrated by using a nonlinear TVECM. The authors detect that some global gold futures returns volatilities and trading activities are threshold cointegrated but some are not. Hence, the findings determine whether the volatility–volume threshold relation holds across countries and investigate the determinants of cross-country differences in different traders.